Asuhan Keperawatan Anak Pada Pasien Dengan Dengue Haemorrhagic Fever (DHF) Diruang Marwa Rumah Sakit Aisyiyah Pariaman Tahun 2026 - Arifrianti Fadhila; Prima Yoselina; Reska Handayani; Erpita Yanti (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Children are individuals undergoing a process of growth and development that encompasses physical, cognitive, psychological, and social aspects in stages from infancy through adolescence, in order to achieve maturity and realize their optimal potential as adults. Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus transmitted through the bite of the Aedes mosquito. The objective of this study is to provide pediatric nursing care for patients with DHF. This study employed a case study method using the nursing process approach from March 8, 2026, to March 12, 2026, in the Marwa Ward of Aisyiyah Pariaman Hospital. Following an assessment, the identified nursing problems were hyperthermia, acute pain, hypovolemia, and risk of nutritional deficit. Nursing interventions included management of hyperthermia, pain management, hypovolemia management, and nutritional needs management. The results of the case study, obtained after five days of nursing care, showed an improvement in the patient’s condition. This was indicated by a return to normal body temperature, the absence of pain complaints, adequate fluid status, and an increased appetite. Furthermore, the planned and continuous nursing interventions proved effective in addressing the nursing problems that arose.